2022
DOI: 10.1097/dcr.0000000000002624
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Immunofluorescence Imaging Reveals an Immune-Rich Tumor Microenvironment in Mucinous Rectal Cancer Characterized by Increased Lymphocyte Infiltration and Enhanced Programmed Cell Death Protein 1 Expression

Abstract: BACKGROUND:Mucinous rectal cancer is associated with a higher incidence of microsatellite instability and a poorer response to neoadjuvant chemoradiotherapy compared to other subtypes of rectal adenocarcinoma. Immune checkpoint inhibitors are an emerging family of anticancer therapeutics associated with highly variable outcomes in colorectal cancer. Although the immune landscape of mucinous rectal cancer has not been fully explored, the presence of mucin is thought to act as a barrier preventing immune-cell in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This process involves the aberrant regulation of signaling pathways and the crucial role of immune in ltration. At the molecular biology level, dysregulation of various signaling pathways, such as Wnt, MAPK, and PI3K/Akt, results in uncontrolled tumor cell proliferation and impaired apoptotic mechanisms, thereby exacerbating the progression of rectal cancer [28][29][30]. Furthermore, these dysregulated signaling pathways contribute to tumor invasion and migration, providing a molecular basis for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This process involves the aberrant regulation of signaling pathways and the crucial role of immune in ltration. At the molecular biology level, dysregulation of various signaling pathways, such as Wnt, MAPK, and PI3K/Akt, results in uncontrolled tumor cell proliferation and impaired apoptotic mechanisms, thereby exacerbating the progression of rectal cancer [28][29][30]. Furthermore, these dysregulated signaling pathways contribute to tumor invasion and migration, providing a molecular basis for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animals models using colon cancer cell lines (MC38 and CT26) suggested that PD-1 upregulation on T cells following (C)RT has rather unfavorable effects on T cell activation and anti-tumor response [199,233]. In human mucinous rectal cancer patients, the use of nCRT and high PD-1 were positively correlated [234]. Furthermore, in a small study including 13 LARC patients who had received SCRT, it could be found that poor responders had an increased number of CD4 + /CD25 hi+ /FOXP3 + /PD-1 + Tregs infiltrating the tumors compared to good responders [198].…”
Section: B Lymphocytesmentioning
confidence: 91%
“…Kim et al 7 evaluated the effect of lymphatic, venous, and perineural invasion and tumor budding on 5-year disease-free and overall survival in patients with LARC undergoing neoadjuvant chemoradiation. Duggan et al 8 reported a study aiming to characterize the immune microenvironment of mucinous rectal cancers in hopes of better defining potential therapeutic targets. Engel et al 9 conducted a retrospective analysis from an Australian cancer database from 3 institutions to determine the prognostic effect of anastomotic leak on disease-free and overall survival.…”
Section: Assessments Of Markers Of Prognosismentioning
confidence: 99%